Organic Reactions 1989
DOI: 10.1002/0471264180.or037.02
|View full text |Cite
|
Sign up to set email alerts
|

The Electrophilic Substitution of Allylsilanes and Vinylsilanes

Abstract: Allylsilanes and vinylsilanes usually react with electrophiles to give substitution. These reactions are conveniently understood as the reactions of alkenes that have been significantly but only slightly modified by the presence of the silyl group. In both reactions, substitution is favored over addition, and both the site of attack and the site of the double bond in the product are usually determined by the site of the silyl group in the starting material. In this chapter only the electrophilic subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
233
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(239 citation statements)
references
References 707 publications
6
233
0
Order By: Relevance
“…Our strategy for its synthesis is illustrated in Chart 8. We reasoned that the complete carbon framework of 60 would be constructed by an intramolecular Hosomi-Sakurai reaction 49,50) of the substrate 61 possessing allylsilane and p-benzoquinone moieties. Since the conjugate addition cyclization leading to the formation of oxaspirocycles had never been reported, the potential conversion intrigued us.…”
Section: )mentioning
confidence: 99%
“…Our strategy for its synthesis is illustrated in Chart 8. We reasoned that the complete carbon framework of 60 would be constructed by an intramolecular Hosomi-Sakurai reaction 49,50) of the substrate 61 possessing allylsilane and p-benzoquinone moieties. Since the conjugate addition cyclization leading to the formation of oxaspirocycles had never been reported, the potential conversion intrigued us.…”
Section: )mentioning
confidence: 99%
“…Since the previous examples of our tandem Pummerer/iminium ion cyclization involve aromatic pbonds, we decided to study several systems which possess a simple olefinic tether. The well documented reactivity of allylsilanes towards electrophiles 31 suggested that the acid promoted reaction of sulfinylenamide 61 should provide access to a bicyclic lactam. Indeed, treatment of 61 with pTsOH afforded the cyclized product 62 in 61% yield (Scheme 13).…”
Section: Scheme 10mentioning
confidence: 99%
“…Changes in the reaction procedure (particularly solvent and temperature changes) could minimize but not completely suppress this. Any traces of water were manifested by the formation of isopropoxysilanes 6, which, after subsequent complete hydrolysis of the reaction mixture, gave 2-propanol and 7 …”
Section: Preparation Of the Allylsilyl Trcflatementioning
confidence: 99%
“…The normal mechanism for electrophilic attack at allylsilanes5 is anti-SE2' (7) in which case the silyl group does not directly interact with the electrophile.Lewis acid complex 8 (Fig. 1).…”
Section: Reaction Of 2 With Electrophilesmentioning
confidence: 99%
See 1 more Smart Citation